Neuroendocrine evidence for dopaminergic actions of hypericum extract (LI 160) in healthy volunteers. - Franklin, M; Chi, J; McGavin, C; Hockney, R; Reed, A; Campling, G; Whale, R; Cowen, P (1999)
BACKGROUND: We studied the effect of a single dose of a formulation of a methanolic extract of Hypericum perforatum (HP), also known as St. John's wort, on plasma concentrations of growth hormone (GH), prolactin (PRL), and cortisol (CORT) in 12 healthy male volunteers. METHODS: Subjects received 9 tablets of the finished product Jarsin 300 and placebo in a double-blind, balanced-order, cross-over design. RESULTS: Following HP relative to placebo, there was a significant increase in plasma GH and a significant decrease in plasma PRL. Plasma CORT levels were unchanged. CONCLUSIONS: Taken together with data from animal experimental studies, the findings suggest that this dose of HP may increase some aspects of brain dopamine function in humans.